Businessmen and ministers of the king in the viceroyalty of New Spain in the 17th century (Simón Váez Sevilla and Don García Valdés y Osorio) - Pulido Serrano, Ignacio (Huarte de San Juan. Geografía e Historia, 2020)
This paper studies the relations between the Portuguese nation’s businessmen and the nobles and ministers of the viceroyalty of New Spain during the 17th century. Through the study of a specific case, such as the relationship between the merchant Simón Váez Sevilla and the nobleman García de Valdés, some of the fundamental elements that constituted such relationships and their evolution over timeuntil the political crisis that took place in Mexico in the 1640s will be examined. This study aims to show fundamental aspects of the process of integration and social promotion experienced by the Portuguese population in Mexican society, as well as the limits of this process.
Keywords: Inquisition; Mexican Holy Office; New Spain viceroyalty; new Christians; seventeenth century